PENGEMBANGAN KAWASAN KONSERVASI HERITAGE KAMPUNG MELAYU, KOTA SEMARANG - Monica, Mery; Ayu, Anggun Putri; Purnawan, Boby Indra (LPPM Universitas Muhammadiyah Jambi, 2024)
Cultural heritage conservation plays a vital role in the sustainable development of cities. It has been recognized worldwide as one of the key considerations in urban planning efforts. Kampung Melayu is one of the heritage areas in Semarang, as stated in the Semarang City Regional Regulation No. 14 of 2011 concerning the City Spatial Plan for 2011-2031. However, due to modernization, this area has experienced physical, economic, and social degradation, resulting in a decline in vitality and the loss of its historical value. This study employs a qualitative research method with a case study approach, requiring spatial delineation, in-depth data collection, and various sources of information. The research is conducted by analyzing existing problems and interpreting them through fundamental theoretical frameworks. The development recommendations for the Kampung Melayu conservation area are based on policy analysis, an assessment of heritage significance, conservation planning analysis, and heritage conservation development. Heritage areas play a crucial role in urban conservation, not only serving as city identities but also as foundations for sustainable development, connecting the past and the present. Therefore, this study is expected to provide insights and recommendations regarding buildings that should be conserved and protected as part of preserving historical appreciation.